The effect of mechanical stress on cartilage energy metabolism. - Lee, R; Wilkins, R; Razaq, S; Urban, J (2002)
Cartilage is routinely subjected to varying mechanical stresses which are known to affect matrix turnover by a variety of pathways. Here we show that mechanical loads which suppress sulphate incorporation or protein synthesis by articular chondrocytes, also inhibit rates of oxygen uptake and of lactate production. Although the mechanisms have not been definitively identified, it has been shown that high hydrostatic pressures reduce the activity of the glucose transporter GLUT. Furthermore, fluid expression consequent on static loading changes intracellular pH and ionic strength; intracellular changes which would reduce the activity of glycolytic enzymes. Both pathways would thus lead to a fall in rates of glycolysis and a reduction in intracellular ATP, and - since ATP concentrations directly affect sulphation of proteoglycans - a rapid fall in sulphate incorporation. Our results suggest that load-induced changes in matrix synthesis in cartilage can occur by means other than changes in gene expression.